How Empirical Research in Human Cognition Does and Does Not Affect Philosophical Ethics - Bowie, Norman E. (Journal of business ethics, 2009)
In this essay, I consider the implications for traditional philosophical ethics posed by discoveries in brain research or neurocognition as well as psychological discoveries concerning human biases and cognitive limitations presented in behavioral economics. I conclude that although there still is much for philosophical ethics to do, the empirical research shows that human freedom and responsibility for ethical decisions is somewhat diminished and that choice architecture and nudges through public policy become important for getting people to do the right thing.